Construction and Restoration of The Waterlines of City Medina in Ottoman Period - Tekin, Zeki (Journal of History Culture and Art Research, 2020)
Medina, one of the most sacred places of the Hejaz region, is seen to have not experienced serious water shortages throughout history. Ayn al-Zarka, one of the most important water springs, and other water reserves meet most of Medina’s needs. The local governments and the Ottoman central government took serious interest in the water issues of the region (especially in Medina), which had been under Ottoman rule for a long time and took the necessary measures. Repair and maintenance of the waterlines, which had deteriorated over time, were closely dealt with, and large-budget cost expenditures were compensated for by the central treasury and/or the Egyptian treasury. Additional water sources were sought to eliminate the water shortages caused by population increases and drought; this was attempted with respect to the periodic needs. The holy places that got particularly crowded during the Hajj season were seen to face water shortages. In recent times, distilling seawater has been attempted as a solution to eliminate this shortage.